Exploration and Characterization of Grain Morphology and Rice (caryopsis) Genotypes of Local Rice in Solok Regency, West Sumatra - Vera Septaria; Musliar Kasim; Irfan Suliansyah; Auzar Syarif; Juniarti Juniarti (Jurnal Biologi Tropis, 2023)
South Solok Regency is one of the potential areas for rice development in West Sumatra Province. The local rice in South Solok Regency is a type of rice that can potentially be developed for germplasm conservation. One genetic resource that needs to be developed is abiotic and biotic resistance to conserve germplasm so that the local rice plants in South Solok can be maintained on certain lands. The first step that must be taken in conservation efforts is to find, identify and collect local rice genotypes in South Solok Regency. This study aimed to explore and characterize the morphology of local grain and rice in Solok Selatan Regency. This study used a survey method, and the exploration location was determined by purposive sampling. The survey results found 18 local South Solok rice genotypes from four sub-districts. The results of grain morphological characterization showed differences in quantitative properties (length, width, thickness, and weight of 100 grains of grain and caryopsis and grain tail length) as well as differences in qualitative characteristics (lemma and palea color, rice color (caryopsis) and shape, rice (caryopsis). Dendrogram results from cluster analysis of 18 local rice genotypes of South Solok, the coefficient of similarity was between 0.27 – 0.64 (27 -64%) with the highest similarity coefficient of genotypes G013 (rambuman variety) and G016 (redek sangir variety) with a value of 0.64 (64%).